VISIONARY YOUNG EDUCATIONAL LEADER (STUDI FENOMENOLOGIS GAYA KEPEMIMPINAN VISIONER KETUA YAYASAN SASMITA JAYA SEBAGAI GENERASI KEDUA PENGELOLA UNIVERSITAS PAMULANG) - Zahiya, Fairuz Niswi Zahiya; Al Faruq, Ubaid Al Faruq; Anwar, Saiful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of visionary leadership exercised by the Chairperson of the Sasmita Jaya Foundation in the management of Universitas Pamulang, particularly in terms of visionary leadership characteristics, forms of support and challenges, as well as leadership experiences encompassing feelings, beliefs, and perceptions. This study employs a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observations, and document analysis involving key informants consisting of the Foundation Chairperson, the Rector, and Vice Rectors, as well as supporting informants including senior lecturers, deans, and heads of institutional units. The findings indicate that the leadership of the Foundation Chairperson reflects key characteristics of visionary leadership, including vision formulation through the development of a long-term vision oriented toward upholding educational integrity and the Tridharma of higher education; vision communication through consistent dissemination of the vision to all stakeholders; commitment to vision as reflected in the consistency of strategic policies; collaboration and empowerment through the active involvement of academic members and external partners; strategic responsiveness and innovation in responding to institutional dynamics through programmatic initiatives and digital development; and value-driven leadership grounded in humanistic and religious values. Support for visionary leadership is developed through participatory mechanisms, including the alignment of strategic policies and programs, active engagement of the academic community, and collaboration with internal and external stakeholders. The challenges identified include intergenerational differences as internal challenges and government regulations as external challenges. Furthermore, the findings reveal that the leadership experience of the Foundation Chairperson is characterized by courage, confidence, and high awareness; a strong belief in achieving the institutional vision through an optimistic attitude while upholding educational integrity and humanistic and religious values; and a self-perception as a responsive and innovative leader who acts as a reformer while maintaining continuity with the founder’s values.